Formulation and Evaluation of Ranitidine Floating Tablets - verma, Anamika; Verma, Priyanka; Khinchi, M. P.; Soni, S. L. (Asian Journal of Pharmaceutical Research and Development, 2015)
The gastroretentive drug delivery systems can be retained in the stomach and assist improving the oral sustained delivery of drugs that have an absorption window in a particular region of the gastrointestinal tract. These systems help in continuously releasing the drug before it reaches the absorption window, thus ensuring optimal bioavailability. This research article describes the preparation and in vitro evaluation of floating tablet of ranitidine hydrochloride by direct compression technique using different concentrations of different grades of polymers (HPMC K4 M and HPMC K100 M) with sodium bicarbonate and citric acid, magnesium stearate and talc Sodium bicarbonate and citric acid were incorporated as gas generating agents. Tablets were prepared by direct compression technique. The tablets were characterized by lag time, floating time, weight variation, and drug content. The results indicated that combination of polymers of both synthetic and natural polymers shows the best result.